Effects of carvedilol treatment on cardiac cAMP response element binding protein expression and phosphorylation in acute coxsackievirus B3-induced myocarditis - Li-Sha, Ge (BioMed Central, 2013)
BACKGROUND: The role of β-adrenergic stimulation on viral myocarditis has been investigated in animal models of viral myocarditis. Excess stimulation of β-adrenergic receptors by catecholamines causes phosphorylation/activation of cAMP response element binding protein (CREB) by the cAMP signaling pathway. CREB as an important regulator of gene expression mediates the cardiovascular remodeling process and promotes anti-inflammatory immune responses. However, the CREB expression and phosphorylation have not been studied, and the effects of carvedilol (a nonselective β-adrenoceptor antagonist) on the CREB has not been investigated in the setting of acute viral myocarditis. METHODS: This study was therefore designed to examine the effects of carvedilol on the transcriptional factor CREB in a murine model of acute viral myocarditis. In a coxsackievirus B3 murine myocarditis model (Balb/c), effects of carvedilol on plasma noradrenaline, heart rate and blood pressure, myocardial histopathological changes and fibrosis, cardiomyocyte apoptosis, cardiac CREB and phosphorylated CREB, cytokine levels, and viral RNA were studied. RESULTS: The expression and phosphorylation of CREB were decreased with concomitant increase of IL-6 and TNF-α in murine coxsackievirus-induced acute viral myocarditis. The levels of IL-6 and TNF-α were correlated with the expression of CREB or phosphorylated CREB. Carvedilol increased the cardiac CREB expression and phosphorylation and decreased the plasma catecholamine levels and the production of IL-6 and TNF-α with amelioration of acute viral myocarditis. CONCLUSION: These results show that CREB may be involved in the pathophysiology of viral myocarditis and carvedilol exerts some of its beneficial effects by increasing the CREB expression and phosphorylation.